2016
DOI: 10.1371/journal.pone.0157975
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Paleoclimatic Events on Mediterranean Trout: Preliminary Evidences from Ancient DNA

Abstract: In this pilot study for the first time, ancient DNA has been extracted from bone remains of Salmo trutta. These samples were from a stratigraphic succession located in a coastal cave of Calabria (southern Italy) inhabited by humans from upper Palaeolithic to historical times. Seven pairs of primers were used to PCR-amplify and sequence from 128 to 410 bp of the mtDNA control region of eleven samples. Three haplotypes were observed: two (ADcs-1 and MEcs-1) already described in rivers from the Italian peninsula;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Several precautions to avoid sample contamination were used as reported in Splendiani et al . (). Genomic DNA was extracted following an ad hoc protocol for formalin‐fixed tissues (Campos & Gilbert, ).…”
Section: Information About Museum Specimens Studied and D‐loop Diagnomentioning
confidence: 99%
See 3 more Smart Citations
“…Several precautions to avoid sample contamination were used as reported in Splendiani et al . (). Genomic DNA was extracted following an ad hoc protocol for formalin‐fixed tissues (Campos & Gilbert, ).…”
Section: Information About Museum Specimens Studied and D‐loop Diagnomentioning
confidence: 99%
“…Six pairs of primers designed by Splendiani et al . () were used to amplify overlapping fragments, ranging in size from 108 to 151 bp (primers included). This region of the mtDNA was chosen as it contains several single nucleotide polymorphism (SNP) diagnostics for the main S. trutta mtDNA lineages initially described by Bernatchez () and successively confirmed by various studies (Cortey et al ., ; Snoj et al ., ; Meraner et al ., ).…”
Section: Information About Museum Specimens Studied and D‐loop Diagnomentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, multiple studies have reported the successful retrieval of aDNA from archaeological fish bone for a variety of species, locations and age (Oosting et al, 2019). aDNA has been consistently amplified from herring (Speller et al, 2012), Pacific salmon (Grier et al, 2013; Johnson et al, 2018; Royle et al, 2018; Speller et al, 2005; Yang et al, 2004), Atlantic cod (Hutchinson et al, 2015; Ólafsdóttir et al, 2014), sturgeon (Ludwig et al, 2009; Nikulina & Schmölcke, 2016; Pagès et al, 2009), Mediterranean trout (Splendiani et al, 2016), Northern pike (Wooller et al, 2015), and other fish taxa (Arndt et al, 2003; Ciesielski & Makowiecki, 2005; Živaljević et al, 2017), in some cases from bones up to 6,000 yBP or older (Johnson et al, 2018; Nikulina & Schmölcke, 2016; Speller et al, 2012; Splendiani et al, 2016; Wooller et al, 2015; Yang et al, 2004). Fish aDNA has also been successfully amplified in metagenomic analyses using bulk bone approaches, even from warm tropical climates (Grealy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%